Recent advances in the combination of cellular therapy with stem cells and nanoparticles after a spinal cord injury - García, Elisa; Sánchez-Noriega, Samantha; González-Pacheco, Guadalupe; González-Vázquez, Alejandro Naat; Ibarra, Antonio; Rodríguez-Barrera, Roxana (Frontiers in Neurology, 2023)
Background: Currently, combined therapies could help to reduce long-term sequelae; stem cell therapy at the site of injury is a well-studied area. If these cells are combined with other therapies, very promising results can be obtained and transferred to the clinic. Nanoparticles (NPs) are versatile nanotechnologies with applications in medical and therapeutic research that can offer efficient treatments, since they have the potential to deliver therapeutic molecules to the target tissue, reducing the side effects of non-targeted therapies. This article purposes to analyze and provide a brief description of the different types of cellular therapies in combination with NPs, and their role as innovative treatments for their regenerative effect after spinal cord injury. Methods: We searched the literature published by Web of Science, Scopus, EBSCO host and PubMed, which researched combinatory therapy for motor impairment following SCI. The search period is from the establishment of the database to December 2022. Result: The combination of NPs plus stem cells has been showed important results on neuroprotection and neuroregeneration. Further studies are needed to understand more about its effects and benefits in SCI on clinical level, we believed that it necessary found and select the molecule most effective by exacerbate the neurorestorative effects of the different stem cells and then probed on patients after SCI. On the other hand, in this review we visualized that PLGA NPs could be the first nanoparticle on combination with stem cells like a therapeutic strategies on patients with SCI, because this NPs has been showed important advantages compared with other NPs as approval by FDA, this is biodegradable, has been reported low toxicity, has high biocompatibility, the research could have control on release time, biodegradation kinetics and the most important its use as nanomaterial on another clinical pathologies (12 studies on www.clinicaltrials.gov) has been probed. Conclusion: The use of cellular therapy and NPs could be an interesting alternative for SCI therapy; however, with the knowledge of possible interventions after SCI promote to have an important variability of molecules used on NPs, what limits have a research direction that permit the advance on this line.